1999
DOI: 10.1177/107110079902000405
|View full text |Cite
|
Sign up to set email alerts
|

Results After Cheilectomy in Athletes with Hallux Rigidus

Abstract: From 1987 to 1993, 20 athletes (22 feet) underwent cheilectomy for Regnauld grade I, grade II hallux rigidus. Average age was 31 years (10 men and 12 women); mean follow-up was at 5.1 years. All patients performed high-level sports (judo, track & field, soccer, and skating). Indications for surgery included failure of nonsurgical treatment with persistent pain during sports activities, shoefitting problems, and recurrent bursitis. The aim of our study was to evaluate the results clinically, radiographically, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 12 publications
1
56
0
5
Order By: Relevance
“…Diagnosis of HR is based on the presence of pain and stiffness in the first MTP joint and physical findings of restricted joint motions, especially dorsiflexion (to <30°), increased joint bulk (due to capsular thickening, swelling and osteophytes) dorsally and associated synovitis (swelling, pain and tenderness) (2). However, the following conditions may confuse the clinical situation at times.…”
Section: Differential Diagnosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosis of HR is based on the presence of pain and stiffness in the first MTP joint and physical findings of restricted joint motions, especially dorsiflexion (to <30°), increased joint bulk (due to capsular thickening, swelling and osteophytes) dorsally and associated synovitis (swelling, pain and tenderness) (2). However, the following conditions may confuse the clinical situation at times.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…HR disability is greater than that seen with HV (2). It is a degenerative arthritis of the first metatarsophalangeal (MTP) joint (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an exhaustive review of the literature, we found no published outcome studies looking at hallux rigidus surgery in active duty military and scarce published studies looking at athletes. Mulier et al 20 published a study looking at athletes who had a cheilectomy procedure performed, and with a 5-year follow-up, they reported that 10% of the patients were unable to return to their sport because of the procedure and had an RTA of 11.5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the outcome of cheilectomy on high level athletes demonstrated 95% good or excellent results, and found the procedure to be reliable in this population because it increases joint motion, maintains stability, avoids loss of purchase power, and permits an early return to sport activity [Mulier et al, 1999]. Mann and Clanton reported 90% patient satisfaction with the procedure and an average 20° of dorsiflexion improvement [Mann & Clanton, 1988].…”
Section: Cheilectomymentioning
confidence: 99%